1980
DOI: 10.1007/bf00473064
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of histoplasmosis: Humoral and cellular activity from a polysacchari-de-protein complex and its deproteinized fraction in experimentally immunized mice

Abstract: In a previous publication it was reported that a polysaccharide-protein complex (PPC), sensitive to beta-glucosidase, was isolated from Histoplasma capsulatum. This complex was strongly reactive in an agar gel diffusion assay with sera from patients with histoplasmosis, but was unreactive with sera from patients with coccidioidomycosis. Here, the studies with human sera have been expanded and attempts were made to determine the response of mice immunized with nonviable H. capsulatum or Coccidioides immitis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Galactomannan-protein complexes from the mycelial phase cell wall of H. capsulatum have antigenic properties; they can induce delayed-type hypersensitivity in guinea pigs and inhibit macrophage migration factor release , Reiss et al 1974. A deproteinized polysaccharide-protein complex isolated from H. capsulatum, which immunolocalized mainly to the mycelial phase cell wall by colloidal gold labelling (Taylor & Bojalil 1977, Taylor et al 1980, Pereira-Morales et al 1998, shares common characteristics with the galactomannan-protein complex reported by Reiss et al (1974). Fungal galactomannan complexes may be involved in a mechanism to protect the organism against its own serinethiol protease, an enzyme associated with pathogen dissemination through the extracellular matrix, as described in paracoccidioidomycosis (Matsuo et al 2006).…”
Section: The Chemical Characteristics and The Functions Of H Capsulamentioning
confidence: 84%
“…Galactomannan-protein complexes from the mycelial phase cell wall of H. capsulatum have antigenic properties; they can induce delayed-type hypersensitivity in guinea pigs and inhibit macrophage migration factor release , Reiss et al 1974. A deproteinized polysaccharide-protein complex isolated from H. capsulatum, which immunolocalized mainly to the mycelial phase cell wall by colloidal gold labelling (Taylor & Bojalil 1977, Taylor et al 1980, Pereira-Morales et al 1998, shares common characteristics with the galactomannan-protein complex reported by Reiss et al (1974). Fungal galactomannan complexes may be involved in a mechanism to protect the organism against its own serinethiol protease, an enzyme associated with pathogen dissemination through the extracellular matrix, as described in paracoccidioidomycosis (Matsuo et al 2006).…”
Section: The Chemical Characteristics and The Functions Of H Capsulamentioning
confidence: 84%
“…A deproteinized polysaccharide‐protein complex of Histoplasma (DPPC‐Histo), as described elsewhere [14], was used as antigen for dot‐ELISA. The purified DPPC‐Histo (50 ng 20 μl −1 of protein) was applied in separate wells to a 0.45 μm nitrocellulose membrane narrow strip (BioTrace, GelmanSciences, Inc. MI, USA) using a 96‐well microfiltration Bio‐Dot apparatus (Bio‐Rad, Richmond, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Crude antigens, histoplasmin, paracoccidioidin, coccidioidin, aspergillin, and candidin, were prepared from culture filtrates [ 1 1 -131, previously standardized in the laboratory for different test conditions [12,14,151.…”
Section: Antigemmentioning
confidence: 99%